Callose synthesis at the center point of plant development-An evolutionary insight - Ušák, David; Haluška, Samuel; Pleskot, Roman (Plant physiology, 2023)
Polar callose deposition into the extracellular matrix is tightly controlled in time and space. Its presence in the cell wall modifies the properties of the surrounding area, which is fundamental for the correct execution of numerous processes such as cell division, male gametophyte development, intercellular transport, or responses to biotic and abiotic stresses. Previous studies have been invaluable in characterizing specific callose synthases (CalSs) during individual cellular processes. However, the complex view of the relationships between a particular CalS and a specific process is still lacking. Here we review the recent proceedings on the role of callose and individual CalSs in cell wall remodelling from an evolutionary perspective and with a particular focus on cytokinesis. We provide a robust phylogenetic analysis of CalS across the plant kingdom, which implies a 3-subfamily distribution of CalS. We also discuss the possible linkage between the evolution of CalSs and their function in specific cell types and processes.
Keywords: Glucosyltransferases; glukany; glukosyltransferasy; vývoj rostlin; Glucans; Plant Development; Phylogeny; fylogeneze; Arabidopsis